Women´s participation in the notarial function: notary or notary/inclusive language - Aragón Salcido, María Inés (UNIVERSIDAD DE SONORA, 2019)
Through the examination of Jurisprudence, human rights incorporated in our National Constitution and their counterparts of the federative entities, thenational and local legislation as the Sonora State and certain national and foreign works related to the gender issue, it is concluded that it is urgent the intervention of the Mexican notarial guildin order to demand the intervention of the local congresses on harmonization of the corresponding legislation, to incorporate the gender perspective, to use an inclusive language and to make women visible in the notarial function in our country.